Pertencimento étnico-racial e ensino de História - Andrade, Paulo Sérgio de (2006)
This research is related to the influence of Teaching of History to build the sense of embrace their ethnic-racial roots and the relation between blacks and whites. It has participated in this research four former black students of an Affirmative Action project who took place in the city of Sao Carlos, state of Sao Paulo, which aimed to prepare students to College admission exams. This research was performed and guided by the following research inquiry: Does the teaching of History contribute to the affirmation/denial to the ethnic-racial feeling of poor black students in the college admission courses? The study takes off from the observations made by the researcher in charge for the subjects of History and Geography in this project. He aimed to verify whether the teaching of History interferes in the self esteem and identity of afro-descendants students, leading them to the feeling of denying their own ethnic racial roots, which is fabricated in the society. Systematic talks with two former female students and two male students were conducted involved in the Affirmative action project that was developed in the period of 2002 and 2003, sponsored by Fundação Ford and attached to Department of Physics of USP, campus Sao Carlos Sao Paulo, aiming to facilitate the access and permanence of poor black students at the public university. It also aimed to strike back situations of prejudice, discrimination and racism such ideas reinforced by ideologies still present along the years in Brazil. The findings showed that the integration of the researched students favored them to embrace the feeling of ethnic and racial roots to what they were alike, when they identify themselves as afro-descendants. These students dealt with racist attitudes and discriminations in their routine. However, they got their self esteem and identity favored by the time they recognized themselves as culture makers and active agents in the scenery of the Brazilian history.